Alih Wahana Cerita Rakyat Legenda Malin Kundang ke Film Animasi - Piliang, Wilda Srihastuty Handayani; Andriyani, Noni (GERAM, 2024)
The digitization of folklore will have a lot of impact, either on folklore itself or even greater on the folklore culture from which it originates. Folktale are the most digitized folklore. Folktale are turned into animated films on social media. As a product of culture, folktale contain local wisdom and values. This is the urgency of this research, whether there are additions, reductions, or varied changes from folktale that are already in written form to the form of animated films on social media like YouTube. Then, how do these additions, reductions, or varied changes affect the existence of the folktale? The theories used are transformation and ecranization. This research is qualitative, with description methods and content analysis techniques. The research data sources are the folktale Legend of Malin Kundang in the book Collection of Indonesian Folk Stories published by Dua Media and the animated film "Legend of Malin Kundang" from the Riri Interactive Children's Stories YouTube channel. The results of the research show that there are reductions, additions, and varied changes from the folklore hipogram of the Malin Kundang legend to the animated film. Then, there was also an expansion, but there was no conversion from the hipogram to the animated film. This research is useful to add to the reference research on transfer of folklore vehicle which is still very minimal.